2010
DOI: 10.1002/micr.20758
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing survival of free‐flap in reconstruction for cancer of the head and neck: A literature review

Abstract: Microvascular free tissue transfer is a reliable technique for head and neck reconstruction with success rates of 90–99%. Currently, there is no consensus concerning antithrombotic agents, antibiotics, or monitoring techniques. Therefore, the aim of this study was to review current literature dealing with microvascular free‐tissue transfer and factors influencing the outcome. In addition to excellent microsurgical techniques, coupling devices are a promising new technique, but are not useful in all arteries. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
113
0
12

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(129 citation statements)
references
References 55 publications
4
113
0
12
Order By: Relevance
“…However, the validity of these risk factors is controversial in the current literature [7,[25][26][27]. Our study also demonstrated a significantly lower rate of SSI in patients treated with penicillins and a significantly higher rate of SSI in patients treated with clindamycin.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…However, the validity of these risk factors is controversial in the current literature [7,[25][26][27]. Our study also demonstrated a significantly lower rate of SSI in patients treated with penicillins and a significantly higher rate of SSI in patients treated with clindamycin.…”
Section: Discussionmentioning
confidence: 45%
“…Nevertheless, the complications associated with free flap reconstruction can be devastating [6][7][8]. Surgical site infection (SSI), one of the most common complications, may lead to vessel thrombosis and, eventually, to flap loss [6].…”
mentioning
confidence: 99%
“…In this setting, the transfer of healthy tissue with a reliable blood supply is of major significance for improving healing. The impact of radiotherapy on flap success rate seems to be negligible (Kruse et al, 2010). The addition of chemotherapy to radiotherapy in the adjuvant treatment doesn't have a significant impact on the success rate, with results comparable to that after radiotherapy alone (Kostrzewa et al, 2010).…”
Section: Risk Factors and Complications Of Free Flap Oral Reconstructionmentioning
confidence: 99%
“…Reconstruction of large defects on the body requires flap surgeries [1][2][3] . The method of choice for reconstructive surgery is always depending on the region involved; however the common interest of such procedures is the flap survival rate 1,4 .…”
Section: Introductionmentioning
confidence: 99%
“…The method of choice for reconstructive surgery is always depending on the region involved; however the common interest of such procedures is the flap survival rate 1,4 . Intraoperative and postoperative monitoring of the microcirculation is a reliable tool for assessment of flap viability after an unavoidable ischemiareperfusion (I/R) injury 5,6 .…”
Section: Introductionmentioning
confidence: 99%